THE POLITICS OF CONFLICT AND INTERNAL DISPLACEMENT: AN ASSESSMENT OF THE INTERNAL AND EXTERNAL CAUSES OF THE LIBERIAN CIVIL WAR - Ojo, Emmanuel Olatunde; Adeâ€™ Agbude, Godwyns (European Scientific Journal, ESJ, 2015)
The perennial status of peace and conflict dialogue in Africa has been very consistent. There is hardly any African States today that is not ridden with one form of internal conflict or the other. Some actions and inactions still have the possibility of generating more conflict in Africa. The possible missing link is that most African States (the leaders and the led) have not learnt the value of learning from history especially the causes and the effects of the Liberian Civil War on its economy, politics, social and citizenry. The Liberian Civil War, which was one of Africa's bloodiest, claimed the lives of more than 200,000 Liberians and further displaced a million others into refugee camps in neighboring countries. Thus, this paper takes a critical look at the incidents of the Liberian Civil War with the intention of critically reflecting on both the internal and the external causes of the war and the countless number of internally displaced people. The paper, dwelling on extensive secondary data, exposes some hidden trajectory to the historical Liberian Civil War with the intention of providing the rest of the African States enough â€œfood for thoughtâ€ and also provide a comprehensive understanding of the causes and the background of displacement in Liberia.